2011
DOI: 10.1016/j.brainres.2011.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic neurons regulate secretion of glial cell line-derived neurotrophic factor by skeletal muscle cells in culture

Abstract: Glial cell line-derived neurotrophic factor (GDNF) has been identified as a potent survival factor for both central and peripheral neurons. GDNF has been shown to be a potent survival factor for motor neurons during programmed cell death and continuous treatment with GDNF maintains hyperinnervation of skeletal muscle in adulthood. However, little is known about factors regulating normal production of endogenous GDNF in skeletal muscle. This study aimed to examine the role that motor neurons play in regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…The inhibition of GDNF production caused by short-term depolarization may explain results of previous studies which show that GDNF production is inhibited when skeletal muscle is co-cultured with cholinergic neurons (Vianney and Spitsbergen, 2011). The inhibitory effect of ACh or short-term electrical stimulation may also help explain why GDNF mRNA levels increase in skeletal muscle following denervation (Lie and Weis, 1998), and why ACh inhibits extra cholinergic nerve branching during development (An et al 2010).…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The inhibition of GDNF production caused by short-term depolarization may explain results of previous studies which show that GDNF production is inhibited when skeletal muscle is co-cultured with cholinergic neurons (Vianney and Spitsbergen, 2011). The inhibitory effect of ACh or short-term electrical stimulation may also help explain why GDNF mRNA levels increase in skeletal muscle following denervation (Lie and Weis, 1998), and why ACh inhibits extra cholinergic nerve branching during development (An et al 2010).…”
Section: Discussionmentioning
confidence: 56%
“…In previous studies we showed that cholinergic neurons play a role in regulating GDNF synthesis and release by skeletal muscle (Vianney and Spitsbergen, 2011). Here, we sought to determine whether cholinergic neurons exert their effect via neurotransmitter release.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations